2022
DOI: 10.1016/j.cgh.2021.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of SARS-CoV-2 Vaccines in Patients With Chronic Liver Diseases (CHESS-NMCID 2101): A Multicenter Study

Abstract: Background and aims We aim to assess the safety and immunogenicity of inactivated whole-virion SARS-CoV-2 vaccines in patients with chronic liver diseases (CLD) in this study. Methods This was a prospective, multi-center, open-label study. Participants aged over 18 years with confirmed CLD and healthy volunteers were enrolled. All participants received 2 doses of inactivated whole-virion SARS-CoV-2 vaccines. Adverse reactions were recorded within 14 days after any dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
109
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(126 citation statements)
references
References 30 publications
10
109
3
2
Order By: Relevance
“…Whether there is a correlation between age and NAb inhibition rate produced by inactivated vaccine needs to be further verified by expanding the sample size. In addition, previous studies have shown that males had lower serological response to SARS-CoV-2 vaccination ( 38 ). Male gender had been implicated in the poor vaccination responsiveness in general population ( 39 41 ).…”
Section: Discussionmentioning
confidence: 95%
“…Whether there is a correlation between age and NAb inhibition rate produced by inactivated vaccine needs to be further verified by expanding the sample size. In addition, previous studies have shown that males had lower serological response to SARS-CoV-2 vaccination ( 38 ). Male gender had been implicated in the poor vaccination responsiveness in general population ( 39 41 ).…”
Section: Discussionmentioning
confidence: 95%
“…While this finding was initially surprising, it is congruent with antibody response studies of patients with and without cirrhosis to SARS-CoV-2 vaccinations, which showed that there were similar rates of neutralizing antibodies generated in CLD patients regardless of presence of cirrhosis. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…57 Recent studies showed that 22.2% of patients with chronic liver diseases (CLD) who received whole virion SARS-Cov-2 vaccines generated no antibody responses and that 24.0% of those who received messenger ribonucleic acid-based (mRNA) SARS-CoV-2 vaccines generated poor [defined as <250U/mL] antibody responses. 8,9 Moreover, multiple previous studies in various large cohorts have demonstrated that SARS-CoV-2 infection in patients with cirrhosis is associated with higher rates of morbidity and mortality. 1014 These data highlight the growing importance of optimizing vaccination strategies for SARS-CoV-2 infection in this vulnerable patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with inflammatory bowel disease (IBD) treated with infliximab were demonstrated to have attenuated antibody responses, 3 as did patients post liver transplantation 4 and those with chronic liver disease. 5 Subsequently, the British Society of Gastroenterology (BSG) has recommended and advocated for booster dosing in these cohorts. 6 As healthcare professionals, we have a duty to promote vaccination in our patient interactions and to continue to contribute to ongoing efforts determining optimal vaccine strategy for the benefit of our patients.…”
mentioning
confidence: 99%
“…However, we have observed suboptimal vaccine responses in some of our gastroenterology patient cohorts. Patients with inflammatory bowel disease (IBD) treated with infliximab were demonstrated to have attenuated antibody responses,3 as did patients post liver transplantation4 and those with chronic liver disease 5. Subsequently, the British Society of Gastroenterology (BSG) has recommended and advocated for booster dosing in these cohorts 6.…”
mentioning
confidence: 99%